Influência da periodontite apical na qualidade de vida relacionada à saúde bucal em uma população rural - Camponogara, Jeanni Gonçalves (2019)
Apical periodontitis is an acute or chronic inflammatory process that affects the alveolar bone in contact with the root apex due to a microbial infection of the root canal system, being one of the main causes of dental visits. Current studies have been evaluating the quality of life related to oral health with the need for endodontic treatment, but there is a lack of studies evaluating the association between AP and OHRQoL. The objective of the present study is to evaluate the impact caused by AP on the quality of life in a rural population from Rosário do Sul, RS. It is a cross-sectional observational study in which data from 584 individuals (18-93 years old) participating in a representative sample of the rural epidemiological survey were analyzed. Based on a periapical assessment on these individuals, AP was evaluated according to the PAI index. To evaluate the OHRQoL of the individuals, the OHIP-14 questionnaire was used. Statistical analysis included descriptive analysis of socio-demographic data using the chisquare test, independent t-test, Mann-whitney test and an analysis of the summary variables for OHIP-14 using the chi-square and Mann-whitney test. As a result, a total mean OHIP-14 score of 8.4 ± 8,68 was found in individuals without AP and 11.23 ± 10,63 in individuals with AP (p = 0.002). Individuals with AP had more impact in the areas of physical pain (p = 0.003), psychological limitation (p <0.001) and handicap (p <0.001). Individuals with AP had a higher mean overall OHIP-14 score, indicating a greater severity of OHRQoL impact in relation to the other individuals. In conclusion, a significant association was found between the presence of AP and worse OHRQoL in individuals living in a rural area.